Traditional Medicine of Japan - Overview of Judo Therapy - Nakagawa, Katsuhiro (International Journal of Applied Science and Engineering (India), 2023)
This study is an excerpt and summary of a doctoral dissertation submitted to the doctoral program at Azteca University international program. This study examines the origin and history of Judo therapy, which is a Traditional Medicine of Japan, and compares it with qualifications similar to Judo therapy in Chiropractic, Osteopathic, and Naprapathy in the United States, and questions its effectiveness and significance. In addition. Traditional Medicine that exists in the world, such as Judo therapy, basically does not require many medical resources, and it can be said that it is an identity rooted in the country or region. As CAM (alternative medicine) is rapidly gaining traction in the business world, reviewing Traditional Medicine and applying it to the present will lead to a reduction in healthcare costs, which is currently a global problem, and to improve the quality of care in countries with few medical resources and fewer doctors.